Systematic Literature Review: The Profitability Of Liquidity Leverage On Company Value - Reiny Erica Sonia; Enggar Diah Puspa Arum; Wira Lestari (International Journal of Economics, Business and Innovation Research, 2025)
Research objectives: This study aims to evaluate the correlation between profitability, liquidity, leverage, and corporate value, while investigating the impact of tax avoidance and Good Corporate Governance (GCG) as additional variables that influence financial performance. Method/Approach: The methodology used is a Systematic Literature Review (SLR), which analyzes eight scientific articles indexed by Sinta and Garuda from 2018 to 2024. Each article is evaluated based on topic relevance, research methodology, and empirical results. Results: The study shows that profitability has a positive and significant impact on firm value, as it indicates a company's ability to generate consistent profits. Liquidity is crucial for maintaining financial stability; however, excessive liquidity can reduce operational efficiency. Leverage has a dual effect: judicious use of debt can increase firm value through the capital multiplier effect, while excessive leverage increases the risk of bankruptcy. Furthermore, tax avoidance affects firm value both directly and indirectly; this strategy can increase short-term profits while creating reputational risks. Governance, culture, and growth (GCG) and business size have been shown to enhance the correlation between financial performance and firm value by encouraging greater transparency and accountability. Practical Implications: practical implications for corporate management to maintain a balance between profitability, liquidity, and leverage. Originality/Novelty: This research has a strong element of novelty compared to previous research because it combines a systematic literature review (SLR) approach with a very specific focus on the relationship between profitability, liquidity, leverage, and firm value during the period 2016–2025.